Tourism marketing: Channel, factor, and strategy for foreign market share in Badung Regency - Nyoman Ariana; I Ketut Sutama; Ida Bagus Gde Pujaastawa; Agung Suryawan Wiranatha; I Gusti Bagus Arya Yudiastina; Wayan Agung Panca P (Journal of Applied Sciences in Travel and Hospitality, 2025)
Badung Regency, a prominent tourism hub in Bali, Indonesia, attracts a diverse range of international tourists. Effective marketing strategies are essential to enhance its competitiveness and address challenges such as traffic congestion and the need for improved digital marketing. This research aims to identify marketing channels and factors, determine key priorities in tourism marketing development, and formulate marketing strategies for international tourist markets in Badung Regency. The study employed a mixed-methods approach, including a literature review, direct and online observation, document analysis, Focus Group Discussions (FGD) and surveys. Data analysis used Importance Performance Analysis (IPA) and Analytical. Hierarchy Process (AHP) methods, supported by SPSS and Expert Choice software. The study identified eight key marketing factors, i.e., tourism products, pricing, tourism image, digital marketing, tourism services, Networking, competitors, and branding, encompassing 48 indicators. Based on IPA, variables are categorized into four quadrants, with 14 indicators in the top priority quadrant. AHP analysis identified ten top marketing strategies, including improving traffic conditions, enhancing online content marketing, strengthening social media marketing, and standardizing tourist services. These strategies are crucial for addressing issues and enhancing international tourism marketing in Badung. The findings highlight the significance of tailoring. Marketing strategies to improve Badung's competitiveness in the global tourism market. The strategic focus on digital marketing, service quality, and brand management can significantly boost tourist satisfaction and loyalty. This research provides a comprehensive framework for developing effective marketing strategies to enhance Badung's appeal as a premier international tourist destination.